Imidazolium and picolinium-based electrolytes for electrochemical reduction of CO2at high pressure - Messias, Sofia (2022)
This work was performed under the project ‘‘SunStorage – Harvesting and storage of solar energy’’, with reference POCI-01-0145-FEDER-016387 and PORLisboa POCI-01-0145-FEDER-016387, funded by European Regional Development Fund (ERDF), through COMPETE 2020 – Operational Programme for Competitiveness and Internationalisation (OPCI), and by national funds, through FCT – Fundação para a Ciência e a Tecnologia I.P. The authors also acknowledge Fundação para a Ciência e a Tecnologia for funding the Project CO2RED under the reference PTDC/EQU-EPQ/2195/2021 and project INIESC National Research Infrastructure in Solar Energy Concentration, FCT_22113 (AAC 01/SAICT/2016), Portugal. Publisher Copyright: © 2022 The Author(s).